Seasonal Co-integration – An Extension of the Johansen and Schaumburg Approach with an Exclusion Test - Tasseven, Ozlem (Panoeconomicus, 2009)
In this paper, the Johansen and Schaumburg method for seasonal cointegration has been tried to be applied for testing an a priori hypothesized cointegrating money demand variable space. We aim to provide a comprehensive discussion of the significance of the variables in the long-run context as stationary relationships for both zero and bi-annual frequencies. For this purpose, several restrictions have been used to impose for identification purposes of the relevant vectors. We also touch upon the possibility that most time series data have been subject to the stochastic seasonality as opposed to the general acceptance in empirical papers. Our results employing data from the Turkish economy show that it is not possible to estimate only a single theory-accepted money demand relationship in the long-run variable space for both zero and bi-annual frequences, but we are able to identify different vectors somewhat consistent with theoretical arguments for the annual frequency.Key words: Seasonality, Co-integration.JEL: B23, C16, C32, C82, E41.